1999
DOI: 10.1104/pp.121.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Starch and the Control of Kernel Number in Maize at Low Water Potentials

Abstract: After reproduction is initiated in plants, subsequent reproductive development is sometimes interrupted, which decreases the final number of seeds and fruits. We subjected maize (Zea mays L.) to low water potentials ( w ) that frequently cause this kind of failure. We observed metabolite pools and enzyme activities in the developing ovaries while we manipulated the sugar stream by feeding sucrose (Suc) to the stems. Low w imposed for 5 d around pollination allowed embryos to form, but abortion occurred and ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
312
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(341 citation statements)
references
References 42 publications
(33 reference statements)
26
312
3
Order By: Relevance
“…Mutations in this gene result in miniature kernels (the mn1 mutation) and have a severely reduced endosperm (Cheng et al, 1996;Vilhar et al, 2002). Recently, the association of a IVR2, a soluble invertase expressed during early kernel development, with seed yield under conditions of limiting photosynthesis suggests that soluble invertases also play a significant role in providing hexose sugars to support cell division during the prestorage phase (Andersen et al, 2002), as has been previously suggested (Zinselmeier et al, 1999).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Mutations in this gene result in miniature kernels (the mn1 mutation) and have a severely reduced endosperm (Cheng et al, 1996;Vilhar et al, 2002). Recently, the association of a IVR2, a soluble invertase expressed during early kernel development, with seed yield under conditions of limiting photosynthesis suggests that soluble invertases also play a significant role in providing hexose sugars to support cell division during the prestorage phase (Andersen et al, 2002), as has been previously suggested (Zinselmeier et al, 1999).…”
mentioning
confidence: 65%
“…Mutations in this gene result in miniature kernels (the mn1 mutation) and have a severely reduced endosperm (Cheng et al, 1996;Vilhar et al, 2002). Recently, the association of a IVR2, a soluble invertase expressed during early kernel development, with seed yield under conditions of limiting photosynthesis suggests that soluble invertases also play a significant role in providing hexose sugars to support cell division during the prestorage phase (Andersen et al, 2002), as has been previously suggested (Zinselmeier et al, 1999).Invertases exhibit complex regulation at the transcriptional and posttranscriptional levels in response to developmental, environmental, and carbohydrate signals (Sturm, 1999). In addition, small (Ͻ20-kD) inhibitor proteins (INVINH) have been associated with invertase preparations in a number of dicot plant species (Pressey, 1994;Weil et al, 1994;Krausgrill et al, 1996Krausgrill et al, , 1998Greiner et al, 1998Greiner et al, , 2000 since their first biochemical characterization (Pressey, 1966;Jaynes and Nelson, 1971).…”
mentioning
confidence: 67%
“…Drought-stressed ovules show decreased vacuolar and cell wall invertase activity, starch depletion and inhibited photosynthesis (Zinselmeier et al 1999). The maize nucellus is supported by the pedicel and cell wall invertase is expressed in the placento-chalaza cell layer which separates the nucellus from the pedicel (Miller and Chourey 1992).…”
Section: Drought Stressmentioning
confidence: 99%
“…The sensitivity of wheat crop to soil drought is particularly important during reproductive and grain-filling period (Zrenner et al 1995;Zinselmeier et al 1999). Water deficit stress during reproductive development restricts the supply of sucrose to floral organs (anthers and young ovaries) and often leads to floral abortion, significantly affecting grain number.…”
Section: Introductionmentioning
confidence: 99%